0.2(x+2)=0.5(x+2)-0.2x-0.4

Simple and best practice solution for 0.2(x+2)=0.5(x+2)-0.2x-0.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.2(x+2)=0.5(x+2)-0.2x-0.4 equation:



0.2(x+2)=0.5(x+2)-0.2x-0.4
We move all terms to the left:
0.2(x+2)-(0.5(x+2)-0.2x-0.4)=0
We multiply parentheses
0.2x-(0.5(x+2)-0.2x-0.4)+0.4=0
We calculate terms in parentheses: -(0.5(x+2)-0.2x-0.4), so:
0.5(x+2)-0.2x-0.4
We add all the numbers together, and all the variables
-0.2x+0.5(x+2)-0.4
We multiply parentheses
-0.2x+0.5x+1-0.4
We add all the numbers together, and all the variables
0.3x+0.6
Back to the equation:
-(0.3x+0.6)
We get rid of parentheses
0.2x-0.3x-0.6+0.4=0
We add all the numbers together, and all the variables
-0.1x-0.2=0
We move all terms containing x to the left, all other terms to the right
-0.1x=0.2
x=0.2/-0.1
x=-2

See similar equations:

| -9w+12w=-15 | | (x-1)^2=16 | | 5(-2x+5)+x-5=-43 | | X²+9x-1620=0 | | t-9-3.2=2 | | 43=y+18 | | 2m2+5m+16=8 | | 2z-z-1=11 | | .25x-5=20 | | 4x/3+7/3=0 | | 4c+6c=10 | | (2x-1)^2=81 | | 1/2(c+3)=2/5c-3/4 | | t+9-9.2=9 | | -20=-4x–6x | | 14=1/3y | | 16x+9=16x-48 | | k+4—5(k+2)=3k—2. | | y²-6=2²+3²-6-(-3) | | -(-13+b)=27 | | 5x+7-3x=1/2(4x+12)+1 | | -44=-14x+28+6x | | 5x+4+3x+10=180 | | F(0)=2x^2+x-1 | | |8-3x|=0 | | 2x+8=5×-3 | | 7w-13=5w-7 | | -6x-18=-72 | | 3/2-w=5/2 | | -7(x+1)=-41x+55 | | -4m+1=-19 | | 5x-16·3x-12=0 |

Equations solver categories